Alfuzosin and Symptoms of Chronic Prostatitis–Chronic Pelvic Pain Syndrome - Nickel, J. Curtis (2008)
BACKGROUND: In men with chronic prostatitis–chronic pelvic pain syndrome, treatment with alpha-adrenergic receptor blockers early in the course of the disorder has been reported to be effective in some, but not all, relatively small randomized trials. METHODS: We conducted a multicenter, randomized, double-blind, placebo-controlled trial to evaluate the efficacy of alfuzosin, an alpha-adrenergic receptor blocker, in reducing symptoms in men with chronic prostatitis–chronic pelvic pain syndrome. Participation in the study required diagnosis of the condition within the preceding 2 years and no previous treatment with an alpha-adrenergic receptor blocker. Men were randomly assigned to treatment for 12 weeks with either 10 mg of alfuzosin per day or placebo. The primary outcome was a reduction of at least 4 points (from baseline to 12 weeks) in the score on the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) (range, 0 to 43; higher scores indicate more severe symptoms). A 4-point decrease is the minimal clinically significant difference in the score. RESULTS: A total of 272 eligible participants underwent randomization, and in both study groups, 49.3% of participants had a decrease of at least 4 points in their total NIH-CPSI score (rate difference associated with alfuzosin, 0.1%; 95% confidence interval, −11.2 to 11.0; P = 0.99). In addition, a global response assessment showed similar response rates at 12 weeks: 33.6% in the placebo group and 34.8% in the alfuzosin group (P = 0.90). The rates of adverse events in the two groups were also similar. CONCLUSIONS: Our findings do not support the use of alfuzosin to reduce the symptoms of chronic prostatitis–chronic pelvic pain syndrome in men who have not received prior treatment with an alpha-blocker.